Development of smart modular lower body support for prolonged standing - Kandasamy, Rajamunirant (2024)
Musculoskeletal diseases (MSD) remain a major source of threat for industry workers. A good understanding and handling musculoskeletal health in the workplace establish a secure and effective working environment. Workers in industry are more likely to have MSD disease in the workplace due to overexertion from manually operating machinery. In this project a metal fabrication company which uses a large number of welders requested to carry out a study and find solution on MSD faced by metal inert gas (MIG) welders. The welders were influenced by prolonged standing when they carried out their daily task which leads to MSD. To overcome the MSD during work, the welders took a long break in interval for recovery which leads the increase of cycle time in producing a product. The aim of this research is to improvise current Modular Lower Body Support in the market which lack of height adjustability and lack of sensor to detect poor bending movements and prolonged sitting. The objectives of this study were to analyze the user’s requirements, technical specifications and ergonomics considerations for developing the Smart Modular Lower Body Support, designing and developing the Smart Modular Lower Body Support and carry out evaluation on the functionality and usability for the Smart Modular Lower Body Support. The current Smart Modular Lower Body is not similar to the other Modular Lower Body Support in the market. The Smart Modular Lower Body Support is a portable product which can be located in any flat desired location. The height of the lower body support is adjustable, solve the height issue of the welders in the industry and well-integrated with Internet of Things (IoT) monitoring system required by the industry. This Smart Modular Lower Body Support is equipped with 2 types of sensors which are load cells and ultrasonic sensors, play a crucial role in identifying the load exerted by the welders on the lower body support and detects the over bending movement of the welders when they carry out their daily task. The IoT system was build up with a notification system connected to cellular phone software, email notification and alarming electronic product such as buzzer and LED. To develop the Smart Modular Lower Body Support, technical data, user’s requirements, ergonomics and work space specifications had been collected at the workplace. House of Quality (HoQ) had been carried out to reflect welder’s idea on the product to be developed. The data that had been gathered were used to design a lower body support using SolidWorks software and been tested with Finite Element Analysis (FEA) to understand how the product behave under various physical condition. The best design had been chosen and fabricated from the analysis of (FEA), (HoQ) and Pugh Matrix Analysis (PMA). The fabricated lower body support had been fixed with a few mechanical parts and electrical components. IoT system had been set up with parameter for internal testing. Finally, the Smart Modular Lower Body Support had been tested in the fabrication industry for evaluation on the functionality and usability. As a result, the cycle time of the welding process had been reduced, MIG welders are free from MSD and the welders can use the Smart Modular Lower Body Support continuously without prolong standing issue. A questionnaire had been carried out with 21 respondents on the usability testing of the Smart Modular Lower Body Support and the usability testing gained a score of 51.31 which stand in the grade of “D” with the acceptability of “OK”.